2013
DOI: 10.1111/asj.12158
|View full text |Cite
|
Sign up to set email alerts
|

Genetic selection for resistance to mycoplasmal pneumonia of swine (MPS) in the Landrace line influences the expression of soluble factors in blood after MPS vaccine sensitization

Abstract: We recently developed a Landrace line that is resistant to mycoplasmal pneumonia of swine (MPS) infection by genetic selection for five generations, and we reported that the immunophenotype of this line is different from that of the non-selected line in terms of changes in peripheral blood leukocyte population after MPS vaccination. This study followed up previous findings demonstrating changes in soluble factors in blood, namely, hormones, Mycoplasma hyopneumoniae-specific immunoglobulin G (IgG), and cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 36 publications
2
24
0
1
Order By: Relevance
“…However, there are no reports on the relationship between Mhp or MPS and IL-17. The present result, in which increased breeding value of IFN-γ concentration corresponded to decreased breeding value of morbid MPS lesions over five generations is supported by the reported IFN-γ response to vaccination with Mhp (Shimazu et al 2014). Therefore, the strong negative genetic correlation between MPS lesions and IL-17 in the present study represents an important finding.…”
Section: Genetic Trendssupporting
confidence: 85%
See 2 more Smart Citations
“…However, there are no reports on the relationship between Mhp or MPS and IL-17. The present result, in which increased breeding value of IFN-γ concentration corresponded to decreased breeding value of morbid MPS lesions over five generations is supported by the reported IFN-γ response to vaccination with Mhp (Shimazu et al 2014). Therefore, the strong negative genetic correlation between MPS lesions and IL-17 in the present study represents an important finding.…”
Section: Genetic Trendssupporting
confidence: 85%
“…The importance of IL-17 in mycoplasmal infection has been reported only for mice (Sieve et al 2009). Shimazu et al (2014) previously reported that IFN-γ concentration in serum after MPS vaccination was significantly higher in the MPS-selected Landrace line compared with a general, non-selected Landrace line. However, an important role of IL-17 in recruitment of the neutrophilic leukocyte in the biophylaxis response to infection is pointed out (Wu et al 2007).…”
Section: Genetic Trendsmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the search for significant and applicable gene variants has developed into an ever-expanding and successful branch of clinical research, including viral (Pseudorabiesvirus [88]; Influenza A (e.g. [143]); bacterial (Haemophilus parasuis [131]; Actinobacillus pleuropneumoniae [93,94]; Mycoplasma hyopneumoniae (e.g., [108]); Streptococcus suis [136]) and parasitic diseases (Sarcocystis [89]; Ascaris suum [100,101]). More than 2,500 quantitative trait loci (QTL) have been published for health parameters in the pig, among them 400 for resistance/susceptibility against a broad range of pathogens (http://www.animalgenome.org/QTLdb/; current status: October 2016).…”
Section: Examples On the Waymentioning
confidence: 99%
“…hyopneumoniae vaccine sensitization (Shimazu et al . , ). The Research and Development Center, Nippon Meat Packers Inc., Japan, improved the Large White breed by selecting for higher peripheral blood immunity over six generations.…”
Section: Introductionmentioning
confidence: 99%